Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1677/joe.1.06364
|View full text |Cite
|
Sign up to set email alerts
|

Locally produced estrogen promotes fetal rat metatarsal bone growth; an effect mediated through increased chondrocyte proliferation and decreased apoptosis

Abstract: The importance of estrogens for the regulation of longitudinal bone growth is unequivocal. However, any local effect of estrogens in growth plate cartilage has been debated. Recently, several enzymes essential for estrogen synthesis were shown to be expressed in rat growth plate chondrocytes. Local production of 17 -estradiol (E2) has also been demonstrated in rat costal chondrocytes. We aimed to determine the functional role of locally produced estrogen in growth plate cartilage. The human chondrocyte-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 48 publications
(44 reference statements)
4
46
0
Order By: Relevance
“…1). These data are in agreement with those from previous studies that showed that E2 could stimulate chondrocyte proliferation and protect against spontaneous apoptosis [2,18]. In addition, lots of evidence has shown that estrogens exert antiapoptotic effects on various cell types such as vascular endothelial, smooth and skeletal muscles, and breast cancer cells [6,17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). These data are in agreement with those from previous studies that showed that E2 could stimulate chondrocyte proliferation and protect against spontaneous apoptosis [2,18]. In addition, lots of evidence has shown that estrogens exert antiapoptotic effects on various cell types such as vascular endothelial, smooth and skeletal muscles, and breast cancer cells [6,17].…”
Section: Discussionsupporting
confidence: 93%
“…Women taking estrogen replacement therapy have a lower than expected risk of OA than controls. However, the possible local effect of estrogens in cartilage has been debated recently, partly due to the unelucidated pathologic mechanism [1,2]. It is widely accepted that chondrocyte apoptosis plays an important role in the pathogenesis of OA, and the regulative mechanism of chondrocyte apoptosis was supposed to be targeted for new treatment strategies for OA [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…(17) Despite the well-known effects of estrogens on longitudinal bone growth, data from in vitro experiments are inconclusive. There are reports of estrogens stimulating, (1,(23)(24)(25) inhibiting, (26,27) or having no effect (28) on chondrocyte proliferation. In addition, it has not yet been possible to evaluate in vivo the role of ERa in growth plate cartilage.…”
Section: J Jbmrmentioning
confidence: 99%
“…(1) Low estradiol (E2) levels enhance skeletal growth during early sexual maturation (ie, the pubertal growth spurt), whereas high E2 levels during late puberty result in growth plate fusion and thereby cessation of longitudinal bone growth in humans. (1,2) The mechanisms of action for these two seemingly opposite effects of estrogens on longitudinal bone growth are not fully understood but clearly depend on maturational stage and serum levels of E2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation